The Chinese liberal spirit : selected writings of Xu Fuguan - Xu, Fuguan; Elstein, David (Professor) (Albany : SUNY Press, 2022)
"Xu Fuguan (1903-1982) was one of the most important Confucian scholars of the twentieth century. A key figure in the Nationalist Party, Xu was involved in the Chinese civil war after World War II and in the early years of the Nationalist government in Taiwan. He never ceased to believe that democracy was the way forward for the Chinese nation. Making his ethical and political thought accessible to English-speaking readers for the first time, these essays analyze the source of morality and how morality must be realized in democratic government; they also provide a sharp contrast to the claim that democracy is not suitable for China--or that Confucian government should be meritocracy, not democracy. They also share the reflections of a man who lived through the Chinese revolution and remained strongly critical of the governments in both the People's Republic of China and Taiwan"--
Part One: Autographical essays. My life of study -- The end of democratic review -- Mourning my enemy, mourning my friend -- Part Two: Ethical and political thought. Two layers of the Chinese political problem -- The construction and advancement of Ruist political thought -- The fundamental character of the Ruist spirit, its limitations, and its rebirth -- The Chinese way of governance : after reading collected writings of Master Lu Xuan -- Between academia and politics -- The culture of the heart-mind -- The creation of the Chinese free society -- The Ruist distinction between cultivating oneself and governing others and its significance -- Why Oppose liberalism? -- The fundamental structure of Mengzi's political thought and the problem of rule of man and rule of law -- The origin of Kongzi's idea of rule by virtue -- The question of Ruist and Daoist personal cultivation in literature.
Includes bibliographical references (pages 317-323) and index.
Translated from the Chinese.
Print version record.
JSTOR
Keywords: Political science -- China -- Philosophy; Confucianism and state -- China; China -- Politics and government -- 20th century; Liberalism; Philosophy, Confucian -- China -- 20th century; Confucianism and state; Confucianisme et État.; Chine -- Politique et gouvernement -- 20e siècle.; Libéralisme.; Philosophie confucéenne -- Chine -- 20e siècle.; liberalism; RELIGION / Confucianism; Confucianism and state; Liberalism; Philosophy, Confucian; Political science -- Philosophy; Politics and government; China